Antiviral activity of natural compounds extracted from Mediterranean medicinal plants against SARS-CoV-2 - Stephanie Ghio; Jean-Pierre Brincat; Yuksel Cetin; Frederick Lia (Academia Biology)
Spices and Mediterranean medicinal plants provide a rich resource for novel antiviral drug development. The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to a pandemic with devastating outcomes, and hence, there is a global need to search for small-molecule inhibitors that can act against this viral pathogen. This review highlights studies that have investigated the antiviral activities of spices and Mediterranean herbs, as well as their mechanism of action against SARS-CoV-2. Potential therapeutic target mechanisms addressed in this review comprise both host-directed and virus-directed therapies. Host-directed therapies include the inhibition of angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2). Virus-directed therapies include inhibition of papain-like protease (PLpro) and the main protease, 3-chymotrypsin-like protease (3CLpro). Though numerous studies have been conducted on natural products, many of these studies have been performed in silico and require further research to verify the suggested therapeutic properties. 3CLpro has been identified as the target with the largest number of proven in vitro results, with compounds from different classes of molecules shown to inhibit this essential viral protease. In silico studies have confirmed the in vitro results, while providing additional mechanistic insights. Phytocompounds can serve as a foundation for designing new antiviral therapies.